STRATEGI KESANTUNAN TINDAK TUTUR DIREKTIF PADA RAPAT BEM FKIP UNIVERSITAS RIAU - Eli Mandari; Charlina Charlina; M.Nur Mustafa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study discribes the use of directive speech act of politeness strategy of participans on the meething of BEM FKIP Riau University. This study used a qualitative approach and description method which it`s aim was to discribe directive speech act of politeness strategy of participans on the meething of BEM FKIP Riau University. The sources of this study is participans on the meething of BEM FKIP Riau University. The data of the study was directive speechs of participants who used positive politeness strategy and negative politeness strategy, based on the theory of politeness strategy of Brown and Levinson. The data was obtained through record technique and validity of the data was acquired through triangulation technique. Then the data was analyzed by indentifying, classifying the data based on the types of directive speechs and positive politeness strategy and negative politeness strategy which were used by the participants on the meeting. In conclusion the use of directive speech act of positive politeness strategy participans on the meething BEM FKIP Riau University was applied by, (1) intensify interest to H; (2) avoid disagreement; (3) presuppose/raise/assert common ground; (4) offer, promise; (5) give (or ask for) reason; and (6) assume or assert reciprocity. On the other hand, directive speech act of negative politeness strategy which was used by the participans on the meething BEM FKIP Riau University was applied by, (1) be conventionally indirect; (2) question, hedge; (3) be pessimistic; (4) minimize the imposition; (5) give deference; (6) apologize; (7) impersonalize S and H; (8) state the FTA as a generale rule; and (9) go on record as incurring a debt, or as not indebting H.Key Word: directive speech act, positive politeness strategy, negative politeness strategy2